2022
DOI: 10.5755/j01.erem.78.2.31006
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Bedul Mangrove Ecotourism Using Green and Fair Strategy Empowerment to Fulfill SDGs 2030 Agenda for Tourism

Abstract: Mangrove management is completely crucial for environmental sustainability. This study aimed (1) to examine the green and fair strategy in developing mangrove ecotourism in Bedul, Banyuwangi Regency, and (2) to examine the economic, social, and cultural improvement of the local community around the mangrove ecotourism area. The research method was qualitative descriptive using Internal Factor Analysis System (IFAS) and External Factor Analysis System (EFAS) matrix analysis from the SWOT approach. Data included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Visitors to the Kondang Merak beach indirectly help to reduce climate change. Visitors engagement in the restoration of damaged and endangered coral reefs presents an opportunity for understanding the significance of preserving the balance of marine ecosystems, reducing destruction, and gaining special and valuable experiences in coral reef conservation activities (Sumarmi et al, 2022). It will create a meaningful experience for tourists (Larsen 2007;Mason & O'Mahony 2007).…”
Section: Methodology and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Visitors to the Kondang Merak beach indirectly help to reduce climate change. Visitors engagement in the restoration of damaged and endangered coral reefs presents an opportunity for understanding the significance of preserving the balance of marine ecosystems, reducing destruction, and gaining special and valuable experiences in coral reef conservation activities (Sumarmi et al, 2022). It will create a meaningful experience for tourists (Larsen 2007;Mason & O'Mahony 2007).…”
Section: Methodology and Datamentioning
confidence: 99%
“…Several studies have reported the importance of edutourism in the tourism industry. Edutourism provides sustainability from various aspects of life (Sumarmi et al 2022). Integrating education into tourism will ensure environmental sustainability (Ioppolo et al 2013;Slocum et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Sampling of data by probability sampling technique or random sampling. All variables in the study were written in the IE matrix, a SWOT analysis was first carried out, the results of which were summarized in the EFAS and IFAS tables (Nusraningrum and Pratama, 2019) (Sumarmi et al, 2022). The methodology of this study can be written as follows as shown in Figure 2.…”
Section: Methodsmentioning
confidence: 99%
“…The tourism sector (Šenková et al, 2022) is expected to be able to drive the people's economy because it is considered the most prepared sector in terms of facilities, infrastructure, and facilities compared to other business sectors. There are various forms of tourism trips (Mohd Shariff, 2022) in terms of the aims and objectives of the tour, namely holiday tourism (Halim et al, 2022), introductory tours, educational tours (Herrera-Franco et al, 2022) and (Sumarmi et al, 2022), knowledge tours, religious tours (Hassan et al, 2022), special interest tours, and hunting tours. The types of tourism studied by researchers are included in knowledge tourism, namely tourism trips whose main purpose is to acquire knowledge or investigate a field of science (Phuthong et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In general, Indonesia's community empowerment strategy surrounding mangrove forests is collaborative mangrove forest management, such as ecotourism activity. Mangrove forest for ecotourism has benefited the economy and ecology (Harahab et al, 2021;Sumarmi et al, 2022;Utami et al, 2022). For example, a small mangrove area in Cirebon district, West Java, Indonesia, provides a suitable habitat for flora and fauna and the potential for an ecotourism site (Purwanto et al, 2021(Purwanto et al, , 2022.…”
Section: Introductionmentioning
confidence: 99%